The Challenges Confronting Public Hospitals in India, Their Origins, and Possible Solutions. (13th July 2014) - Bajpai, Vikas
Abstract : Despite the implementation of National Rural Health Mission over a period of nine years since 2005, the public health system in the country continues to face formidable challenges. In the context of plans for rolling out "Universal Health Care" in the country, this paper analyzes the social, economic, and political origins of the major challenges facing public hospitals in India. The view taken therein holds the class nature of the ruling classes in the country and the development paradigm pursued by them as being at the root of the present problems being faced by public hospitals. The suggested solutions are in tune with these realities.